Sib1, Sib2, and Sib3 proteins are required for ferrichrome-mediated cross-feeding interaction between Schizosaccharomyces pombe and Saccharomyces cerevisiae - Brault, Ariane; Mbuya, Berthy; Labbé, Simon (Frontiers in Microbiology, 2022)
Although Saccharomyces cerevisiae is unable to produce siderophores, this fungal organism can assimilate iron bound to the hydroxamate-type siderophore ferrichrome (Fc) produced and secreted by other microbes. Fc can enter S. cerevisiae cells via Arn1. Unlike S. cerevisiae, Schizosaccharomyces pombe synthesizes and secretes Fc. The sib1+ and sib2+ genes encode, respectively, a Fc synthetase and an ornithine-N5-oxygenase, which are required for Fc production. When both genes were expressed in S. pombe, cross-feeding experiments revealed that S. cerevisiae fet3Δ arn1-4Δ cells expressing Arn1 could grow in the vicinity of S. pombe under low-iron conditions. In contrast, deletion of sib1+ and sib2+ produced a defect in the ability of S. pombe to keep S. cerevisiae cells alive when Fc is used as the sole source of iron. Further analysis identified a gene designated sib3+ that encodes an N5-transacetylase required for Fc production in S. pombe. The sib3Δ mutant strain exhibited a severe growth defect in iron-poor media, and it was unable to promote Fc-dependent growth of S. cerevisiae cells. Microscopic analyses of S. pombe cells expressing a functional Sib3-GFP protein revealed that Sib3 was localized throughout the cells, with a proportion of Sib3 being colocalized with Sib1 and Sib2 within the cytosol. Collectively, these results describe the first example of a one-way cross-feeding interaction, with S. pombe providing Fc that enables S. cerevisiae to grow when Fc is used as the sole source of iron.